Effort Required and Lessons Learned From Recruiting Health Plans and Rural Primary Care Practices for a Cancer Screening Outreach Study - Brittany Badicke; Jennifer Coury; Emily Myers; Amanda F. Petrik; Jean Hiebert Larson; Sombuddha Bhadra; Gloria D. Coronado; Melinda M. Davis (SAGE Publishing, 2024)
Introduction: Recruiting organizations (i.e., health plans, health systems, or clinical practices) is important for implementation science, yet limited research explores effective strategies for engaging organizations in pragmatic studies. We explore the effort required to meet recruitment targets for a pragmatic implementation trial, characteristics of engaged and non-engaged clinical practices, and reasons health plans and rural clinical practices chose to participate. Methods: We explored recruitment activities and factors associated with organizational enrollment in SMARTER CRC, a randomized pragmatic trial to increase rates of CRC screening in rural populations. We sought to recruit 30 rural primary care practices within participating Medicaid health plans. We tracked recruitment outreach contacts, meeting content, and outcomes using tracking logs. Informed by the Consolidated Framework for Implementation Research, we analyzed interviews, surveys, and publicly available clinical practice data to identify facilitators of participation. Results: Overall recruitment activities spanned January 2020 to April 2021. Five of the 9 health plans approached agreed to participate (55%). Three of the health plans chose to operate centrally as 1 site based on network structure, resulting in 3 recruited health plan sites. Of the 101 identified practices, 76 met study eligibility criteria; 51% (n = 39) enrolled. Between recruitment and randomization, 1 practice was excluded, 5 withdrew, and 7 practices were collapsed into 3 sites for randomization purposes based on clinical practice structure, leaving 29 randomized sites. Successful recruitment required iterative outreach across time, with a range of 2 to 17 encounters per clinical practice. Facilitators to recruitment included multi-modal outreach, prior relationships, effective messaging, flexibility, and good timing. Conclusion: Recruiting health plans and rural clinical practices was complex and iterative. Leveraging existing relationships and allocating time and resources to engage clinical practices in pragmatic implementation research may facilitate more diverse representation in future trials and generalizability of research findings.